Post-resuscitation syndrome after cardiac arrest - protecting the brain - Seder, David (Henry Stewart Talks, 2016)
Post-resuscitation disease, Brain injury, Secondary brain injury, Hypothermia after cardiac arrest, Seizure control, Hemodynamic support and cerebral microcirculation, Systemic inflammation